Voluntariado empresarial : sentidos da participação - Dias, Roberta Atherton Magalhães (2008)
The purpose of this work is to analyze the subjective senses in taking part in a volunteering business program for professional volunteers. By assuming that to practice volunteering under the guidelines of an organizational program is incipient, thus cons